How to Avoid Innovation Competence Loss in R&D Outsourcing. (February 2017) - Becker, Markus C.; Zirpoli, Francesco
Companies developing complex products face a crucial dilemma: the benefits of research and development (R&D) outsourcing such as lower costs, access to specialist knowledge, or shorter development lead times often have negative consequences for competence development due to the loss of opportunities for learning by doing. Having experienced the problems of outsourcing R&D, Fiat developed a novel organizational solution that offers new insights as to how firms can organize R&D to protect against innovation competence loss in R&D outsourcing.